Ladybird: topsy + tim meet the ambulance crew - Adamson, Jean; Adamson, Gareth (Ladybird Loughborough, 1998)
Topsy and Tim books are divided into five themes: school; going out; special friends; first experiences; and people who help us. They present fun, factual stories dealing with new experiences and storylines suited to "read to" and older "self read" situations.